Psychiatry and global conflict: a review of war-related psychological impacts, ethical dilemmas, and future directions - Kirolos Eskandar (Debates em Psiquiatria, 2025)
The intricate relationship between psychiatry and global conflict remains an underexplored yet critical area of study, particularly in the context of a potential Third World War. This literature review delves into the psychological roots of conflict, examining how individual and collective psychopathologies contribute to war dynamics and escalation. It highlights the ethical dilemmas faced by mental health professionals in balancing clinical responsibilities with geopolitical influences, including the use of psychiatric knowledge in psychological warfare. The review also explores the mental health implications of prolonged global tensions and technological advancements, such as the rise of cyber-warfare and its psychological impact on populations. Emphasizing the role of psychiatry in fostering peace, this work proposes innovative strategies for leveraging mental health interventions to mitigate conflict and promote resilience in societies facing existential threats. The findings underscore the potential of psychiatry to play a transformative role in preventing and managing the psychological dimensions of future global conflicts.